Real Effects of Hedge Accounting Standards: Evidence from ASU 2017‐12 - ALI, WAQAR; BENS, DANIEL A.; CASSAR, GAVIN (Journal of Accounting Research, 2025)
ABSTRACT Complexity in applying financial accounting standards can have real operational effects if firms alter their actions in response to increased reporting costs. We examine whether the introduction of ASU 2017‐12, designed to reduce compliance burden and better align hedge accounting rules with risk management practices, led to more effective hedging. Using detailed hedging disclosures, we show that firms that adopt the ASU expand the use of hedge‐accounted derivatives and reduce exposures to interest rate and foreign currency risks. ASU‐adopting firms also reduce cash flow volatility, increase their use of debt, invest more, and reduce information asymmetry in the equity market. Our analyses reveal that easing hedge effectiveness tests and reliefs targeting “cash flow hedges” and “net investment hedges of foreign operations” were the most influential of the ASU's reforms. Our study is the first to integrate the effects of hedge accounting frictions on firms’ risk management activities and resulting spillovers to debt financing and investments.